2021
DOI: 10.1002/lary.29632
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fungal Sinusitis in Post COVID‐19 Patients: A New Clinical Entity

Abstract: Objectives Occurrence of invasive fungal respiratory superinfections in patients with COVID‐19 has gained increasing attention in the latest studies. Yet, description of acute invasive fungal sinusitis with its management in those patients is still scarce. This study aims to describe this recently increasing clinical entity in relation to COVID‐19 patients. Study Design Longitudinal prospective study. Methods Prospective longitudinal study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
108
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(145 citation statements)
references
References 43 publications
16
108
1
2
Order By: Relevance
“…In Egypt at the Department of Otorhinolaryngology, Mansoura University, El-Kholy et al [ 57 ] reported a total of 36 patients with fungal rhinosinusitis (AIFR) in the last quarter of 2020 during the second wave of the pandemic. DM was the most common associated risk factor (27.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt at the Department of Otorhinolaryngology, Mansoura University, El-Kholy et al [ 57 ] reported a total of 36 patients with fungal rhinosinusitis (AIFR) in the last quarter of 2020 during the second wave of the pandemic. DM was the most common associated risk factor (27.8%).…”
Section: Discussionmentioning
confidence: 99%
“…We excluded five of these 39 citations, reporting on 2293 cases (3 citations from India [n = 2272], one each from Iran [n = 10], and Egypt [n = 11]), where individual patient details were not available. [25,33,36,37,44]. Finally, we included 275 reported cases of CAM, of which 233 were reported from India and 42 from the rest of the world (most commonly from Iran [n = 19], the USA [n = 9], and others).…”
Section: Epidemiology Of Cam In India Versus the Rest Of The Worldmentioning
confidence: 99%
“…On analyzing the sources of the reported cases, India was the most contributing country (55.5%) [46][47][48][49][50]58,69,77,[80][81][82][84][85][86][87][88], followed by Egypt (17.8%) [72,74], Iran (9.9%) [63,64,70,78], Turkey (6.3%) [65,71], and the United States of America (4.7%) [52][53][54][55][56][57]59,75,76]. See Figure 4.…”
Section: Demographic Characteristicsmentioning
confidence: 99%